(untitled) (JS (JURNAL SEKOLAH), 2019)
Abstract: Analysis of Science Literacy Ability in PGSD Students Semester 1 Academic Year 2019/2020. This research or analysis aims to uncover the cognitive dimensions of scientific literacy consisting of conceptual knowledge, the use of scientific knowledge in analyzing texts or articles, using knowledge or concepts in a meaningful way, analyzing and evaluating data or events, and solving problems. This type of research is descriptive qualitative. The subjects of this study were 100 PGSD students in semester 1 of the 2019/2020 academic year. The instrument used in this study was a scientific literacy question consisting of 15 standard PISA items. Based on the results and discussion it can be concluded that the ability to think (critical and creative) students tend not to develop in science learning. Keywords: scientific literacy, thinking ability Abstrak: Analisis Kemampuan Literasi Sains Pada Mahasiswa PGSD Semester 1 Tahun Akademik 2019/2020. Penelitian atau analisis ini bertujuan mengungkap dimensi kognitif literasi sains yang terdiri dari pengetahuan konsep, penggunaan pengetahuan sains dalam menganalisis teks atau artikel, menggunakan pengetahuan atau konsep-konsep secara bermakna, menganalisis dan mengevaluasi data atau peristiwa, serta memecahkan masalah. Jenis penelitian ini adalah deskriptif kualitatif. Subjek penelitian ini adalah 100 orang mahasiswa PGSD semester 1 tahun akademik 2019/2020. Instrumen yang digunakan dalam penelitian ini, yaitu soal literasi sains yang terdiri dari 15 butir soal standar PISA. Berdasarkan hasil dan pembahasan dapat disimpulkan bahwa kemampuan berpikir (kritis dan kreatif) mahasiswa cenderung tidak berkembang dalam pembelajaran sains. Kata kunci: literasi sains, kemampuan berfikir